PENERAPAN ISAK 35 TENTANG PENGELOLAAN LAPORAN KEUANGAN ENTITAS BERORIENTASI NON LABA Studi Kasus Pada Vihara Dhammadipa Arama Batu Malang - Maria, Evi; Wijaya, Tasya (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2023)
Abstract The presentation of financial reports for non-profit organizations is regulated in the Statement of Financial Accounting Standards (PSAK) 45 since 1997 which was later updated with the Interpretation of Financial Accounting Standards (ISAK) 35 which became effective in 2020. The purpose of this study was to look at the presentation of financial reports at the Dhammadipa Arama Temple accordance with ISAK 35 and its benefits. The type of research used in this study is a descriptive qualitative method with a case study approach. The form of financial reports at the Dhammadipa Arama Batu Temple in 2022 has been adjusted to ISAK 35 which consists of a Comprehensive Income Statement, a Statement of Cash Flows, a Report on Changes in Net Assets, a Report Finance and Notes to Financial Statements. The Dhammadipa Arama Monastery has many benefits that will be obtained by implementing ISAK 35 in financial reports including improving the quality of financial reports, completing elements of financial reports and making it easier to find out surplus (deficit), being able to see how much current assets and non-current assets they have.